Hyaluronic acid and TGF-β1 in dogs with hepatobiliary diseases - Ceplecha, Václav; Řeháková, Kristína; Lendon, Corinne; Proks, Pavel; Škorič, Miša; Grinwis, Guy C. M; Hřibová, Barbora; Vávra, Miloš; Lorenzová, Jana; Crha, Michal (Acta veterinaria Brno, 2018)
The aim of the study was to assess serum hyaluronic acid (HA) and transforming growth factor beta 1 (TGF-β1) concentrations: 1) to differentiate hepatic fibrosis from other forms of liver disease, and 2) for the non-invasive staging of canine liver fibrosis. We also evaluated the association between serum HA concentration and the size of the shunt vessel as an indirect marker of decreased liver clearance in patients with single congenital vascular anomaly. Forty-one healthy client-owned dogs and forty dogs diagnosed with hepatobiliary disease were enrolled in the prospective study. Patients were divided into 4 subgroups: 1) congenital portosystemic shunts (CPSS); 2) parenchymal diseases (a. mild and moderate fibrosis, b. advanced fibrosis and cirrhosis); 3) hepatic neoplasia; 4) biliary tract disorders based on thorough clinical, ultrasound and histopathological examination. Serum HA and TGF-β1 concentrations were measured using ELISA. The HA concentration was significantly increased in patients with advanced liver fibrosis/cirrhosis (P < 0.001) and CPSS (P < 0.001) compared to healthy dogs. Using a cut-off HA concentration of 135.94 ng/ml, the sensitivity and specificity for diagnosis for advanced liver fibrosis/cirrhosis was 100% (95% CI, 50.6–100) and 90.8% (95% CI, 81.6–95.7), respectively. The TGF-β1 levels did not significantly differ among groups (P = 0.180). Negligible correlation was found between serum HA concentration and the size of portosystemic shunt vessel (rs = 0.07; P = 0.831). These findings suggest that serum HA concentration is a potential non-invasive biomarker for advanced liver fibrosis and/or cirrhosis in dogs. The utility of measuring serum concentration of TGF-β1 for diagnosing canine liver fibrosis was not supported.
Keywords: biologické markery; laparoskopie; Digestive System Diseases; ELISA; Hyaluronic Acid; diferenciální diagnóza; prospektivní studie; ROC křivka; senzitivita a specificita; statistika jako téma; Enzyme-Linked Immunosorbent Assay; Liver Diseases; Sensitivity and Specificity; Biopsy; Hepatitis, Chronic; Liver Cirrhosis; psi; transformující růstový faktor beta1; Prospective Studies; Transforming Growth Factor beta1; Biomarkers; Statistics as Topic; ROC Curve; nemoci trávicího systému; biopsie; chronická hepatitida; Dogs; Diagnosis, Differential; nemoci jater; kyselina hyaluronová; jaterní cirhóza; Laparoscopy